EMI shielding polymeric compositions

JP2025504745APending Publication Date: 2025-02-19TICONA LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024534267
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-23
Filing Date
2022-12-21
Publication Date
2025-02-19

Smart Images

  • Figure 2025504745000001_ABST
    Figure 2025504745000001_ABST
Patent Text Reader

Abstract

A polymeric composition is provided that includes a thermoplastic polymer and an electromagnetic interference filler. At a thickness of 3.2 millimeters and over a frequency range of 2 GHz to 18 GHz, the composition may exhibit an average absorption coefficient of about 25% or greater and an average electromagnetic interference shielding effectiveness of about 40 decibels or greater, as determined according to ASTM D4935-18.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 293,226, filed December 23, 2021, which is incorporated herein by reference. [Background technology]

[0002] Radar modules are routinely used in automobiles (e.g., electric vehicles) to detect nearby objects. They can be used in short-range applications, such as blind spot detection, parking assistance, and collision avoidance systems, as well as long-range applications, such as dynamic cruise control and cross traffic alert systems. Radar modules typically include one or more printed circuit boards with dedicated electrical components for handling radio frequency (RF) radar signals, digital signal processing tasks, and the like. To ensure that these components operate effectively, they are typically housed in a housing structure and covered with a radome that is transparent to radio waves. Because other surrounding electrical devices may generate electromagnetic interference (EMI) that may affect the correct operation of the radar module, an EMI shield or shielding (e.g., an aluminum plate) is typically placed between the housing and the printed circuit board. In addition, because the radio signal transmitter antenna is typically placed in close proximity to the radio signal receiver antenna, the transmitted radio waves may be reflected by components in the radar module toward the receiving antenna, causing interference. Therefore, there is a need for materials that can provide both EMI shielding as well as high levels of wave absorption to isolate the transmitting and receiving antennas and eliminate noise in the signals reflected within the module. Additionally, as the automotive industry continues to require smaller and lighter components, materials need to be lightweight while maintaining good mechanical properties. Summary of the Invention [Means for solving the problem]

[0003] According to one embodiment of the present invention, a polymeric composition is disclosed that includes an electromagnetic interference filler distributed within a polymeric matrix that includes a thermoplastic polymer, the composition exhibiting an average absorption of greater than or equal to about 25% and an average electromagnetic interference shielding effectiveness of greater than or equal to about 40 decibels over a frequency range of 2 GHz to 18 GHz at a thickness of 3.2 millimeters, as determined according to ASTM D4935-18.

[0004] According to another embodiment of the present invention, a radar module is disclosed that includes a housing, at least one antenna element mounted in the housing, a shield mounted on a first side of the antenna element, and a radome mounted on the shield, wherein the shield comprises a polymer composition including recycled carbon fibers distributed in a thermoplastic polymer matrix.

[0005]

[0005] Other features and aspects of the present invention are described in more detail below.

[0006] A full and enabling disclosure of the present invention, including the best mode thereof to one skilled in the art, is set forth more particularly in the remainder of the specification, including reference to the accompanying figures. [Brief description of the drawings]

[0006] [Figure 1]

[0007] FIG. 1 is a schematic exploded perspective view of a radar module according to some embodiments of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007]

[0008] Those skilled in the art should understand that this discussion is a description of exemplary embodiments only, and is not intended to limit the broader aspects of the invention.

[0009] Generally speaking, the present invention is directed to a polymeric composition containing an EMI filler distributed within a polymeric matrix containing a thermoplastic polymer. By selectively controlling the specific components of the composition and their relative concentrations, the inventors have discovered that the resulting composition can exhibit unique properties for use in a wide variety of potential product applications, such as electronic modules (e.g., radar modules) and other applications requiring radar absorbing materials. In certain embodiments, for example, the polymeric composition may exhibit an EMI shielding effectiveness ("SE") of about 40 decibels (dB) or greater, in some embodiments about 45 dB or greater, in some embodiments about 50 dB or greater, and in some embodiments about 55 dB to about 100 dB, as determined at high frequencies, such as 6 GHz, according to ASTM D4935-18. In particular, it has been discovered that the EMI shielding effectiveness can remain stable over a high frequency range, such as about 700 MHz or greater, in some embodiments about 1 GHz to about 100 GHz, in some embodiments about 1 GHz to about 20 GHz, such as about 1.5 GHz to about 10 GHz, and in some embodiments about 2 GHz to about 18 GHz. The EMI shielding effectiveness may also be within a desired range for a variety of different component thicknesses, such as about 0.5 to about 10 millimeters, in some embodiments about 0.8 to about 5 millimeters, and in some embodiments about 1 to about 4 millimeters (e.g., 1 millimeter, 1.6 millimeters, or 3.2 millimeters). Within these high frequency and / or thickness ranges, for example, the average EMI shielding effectiveness may be about 40 dB or greater, in some embodiments about 45 dB or greater, and in some embodiments about 50 dB to about 100 dB. Similarly, the minimum EMI shielding effectiveness may be about 10 dB or greater, in some embodiments about 15 dB or greater, and in some embodiments about 20 dB to about 100 dB. The compositions may also have good EMI shielding effectiveness at low frequencies, such as from 30 MHz to 1.5 GHz, for example from 200 MHz to 1.5 GHz.For example, within these low frequency ranges and thickness ranges noted above, the average EMI shielding effectiveness may be greater than or equal to about 50 dB, in some embodiments greater than or equal to about 55 dB, and in some embodiments, between about 60 dB and about 100 dB.

[0008]

[0010] In addition to exhibiting good EMI shielding effectiveness, the composition may also exhibit high radio wave absorptivity within the same high frequency and / or thickness ranges noted above. For example, the composition may have an average absorptivity of about 25% or more, in some embodiments about 30% or more, and in some embodiments about 32% to about 40% at a frequency of 10 GHz. Further, over a range of 1 GHz to 20 GHz, e.g., 2 GHz to 18 GHz, the composition may have an absorptivity of about 25% or more, in some embodiments about 30% or more, and in some embodiments about 32% to about 40% at a thickness of about 1 to about 4 millimeters (e.g., 1 millimeter, 1.6 millimeters, or 3.2 millimeters). Further, in a frequency range of 30 MHz to 1.5 GHz, the composition may have an average absorptivity of about 20% or more, in some embodiments about 23% or more, and in some embodiments about 25% to about 35% at a thickness of about 1 to about 4 millimeters (e.g., 1 millimeter, 1.6 millimeters, or 3.2 millimeters). Further, in the frequency range of 1.5 MHz to 10 GHz, the composition may have an average absorption of about 20% or more, in some embodiments about 25% or more, and in some embodiments about 30% to about 40% at a thickness of about 1 to about 4 millimeters (e.g., 1 millimeter, 1.6 millimeters, or 3.2 millimeters).

[0009]

[0011] It was previously believed that polymer compositions that exhibited good EMI shielding effectiveness and absorption also did not have sufficient mechanical properties. However, it has been discovered that polymer compositions can still maintain excellent mechanical properties. For example, a polymer composition may have an EMI shielding effectiveness of about 2 kJ / m2 as measured according to ISO Test No. 179-1:2010 (technically equivalent to ASTM D6110) at various temperatures, e.g., within a temperature range of about -50°C to about 85°C (e.g., at 23°C). 2In some embodiments, about 4 to about 20 kJ / m 2 In some embodiments, from about 6 to about 10 kJ / m 2 The polymer composition may exhibit a Charpy notched impact strength of about 100 MPa or more, in some embodiments about 150 MPa or more, and in some embodiments about 200 to about 300 MPa; a tensile strain at break of about 0.1% or more, in some embodiments about 0.5% to about 5%, and in some embodiments about 1.0% to about 2.5%; and / or a tensile modulus of about 10,000 MPa to about 50,000 MPa, in some embodiments about 20,000 MPa to about 40,000 MPa, and in some embodiments about 25,000 MPa to about 35,000 MPa. Tensile properties may be determined at various temperatures, for example, within a temperature range of about -50°C to about 85°C (e.g., 23°C), according to ISO Test No. 527-1:2019 (technically equivalent to ASTM D638-14). The polymeric composition may also exhibit a flexural strength of about 150 to about 600 MPa, in some embodiments about 250 to about 500 MPa, and in some embodiments about 300 to about 400 MPa; a flexural strain at break of about 0.5% or greater, in some embodiments about 0.8% to about 5%, and in some embodiments about 1.2% to about 2.5%; and / or a flexural modulus of about 5,000 MPa to about 60,000 MPa, in some embodiments about 20,000 MPa to about 55,000 MPa, and in some embodiments about 25,000 MPa to about 40,000 MPa. Flexural properties may be determined at various temperatures, for example, within a temperature range of about -50°C to about 85°C (e.g., 23°C), according to ISO Test No. 178:2019 (technically equivalent to ASTM D790-17).

[0010]

[0012] The composition may also have good thermal properties. For example, the polymer composition may exhibit a deflection temperature under load (DTUL) of about 150° C. or more, in some embodiments about 200° C., and in some embodiments, about 250° C. to about 300° C., as determined according to ISO 75-2:2013 (technically equivalent to ASTM D648-07) at a specified load of 1.8 MPa. The polymer composition may also be thermally conductive, and thus exhibit, for example, an in-plane thermal conductivity of about 1 W / m·K or more, in some embodiments about 1.5 W / m·K or more, and in some embodiments about 2 to about 10 W / m·K, as determined according to ASTM E 1461-13. The composition may also exhibit a through thickness thermal conductivity of about 0.3 W / m·K or more, in some embodiments about 0.4 W / m·K or more, in some embodiments about 0.5 W / m·K or more, and in some embodiments about 0.7 to about 3 W / m·K, as determined according to ASTM E 1461-13.

[0011]

[0013] Various embodiments of the invention will now be described in more detail. I. Polymer Matrix A. Thermoplastic polymers

[0014] As noted, the polymer matrix may contain one or more thermoplastic polymers. Typically, it is desirable for such polymers to have a high degree of heat resistance, as reflected by a temperature deflection under load ("DTUL") of about 40°C or higher, in some embodiments about 50°C or higher, in some embodiments about 60°C or higher, in some embodiments about 80°C to about 250°C, and in some embodiments about 100°C to about 200°C, as determined at 1.8 MPa according to ISO 75-2:2013. In addition to exhibiting a high degree of heat resistance, thermoplastic polymers also typically have a high glass transition temperature, such as about 10°C or higher, in some embodiments about 20°C or higher, in some embodiments about 30°C or higher, in some embodiments about 40°C or higher, in some embodiments about 50°C or higher, and in some embodiments about 60°C to about 320°C. When semi-crystalline or crystalline polymers are used, the high performance polymers may also have high melting temperatures, such as above about 140° C., in some embodiments from about 150° C. to about 400° C., and in some embodiments from about 200° C. to about 380° C. Glass transition and melting temperatures may be determined using differential scanning calorimetry ("DSC") as determined by ISO 11357-2:2020 (glass transition) and 11357-3:2018 (melting), as is well known in the art.

[0012]

[0015] Suitable thermoplastic polymers for this purpose may include, for example, polyolefins (e.g., ethylene polymers, propylene polymers, etc.), polyamides (e.g., aliphatic, semi-aromatic or aromatic polyamides), polyesters, polyarylene sulfides, liquid crystal polymers (e.g., wholly aromatic polyesters, polyesteramides, etc.), polycarbonates, polyethers (e.g., polyoxymethylene), etc., as well as blends thereof. The exact selection of the polymer system will depend on a variety of factors, such as the nature of other fillers included within the composition, the manner in which the composition is formed and / or processed, and the particular requirements of the intended application.

[0013]

[0016] Aromatic polymers, for example, may be suitable for some applications. Aromatic polymers may be substantially amorphous, semi-crystalline or crystalline in nature. One example of a suitable semi-crystalline aromatic polymer is, for example, an aromatic polyester, which may be a condensation product of at least one diol (e.g., aliphatic and / or cycloaliphatic), such as those having 4 to 20 carbon atoms, and in some embodiments 8 to 14 carbon atoms, with at least one aromatic dicarboxylic acid. Suitable diols include, for example, neopentyl glycol, cyclohexanedimethanol, 2,2-dimethyl-1,3-propanediol, and carboxylic acids of the formula HO(CH2). n OH, where n is an integer from 2 to 10. Suitable aromatic dicarboxylic acids may include, for example, isophthalic acid, terephthalic acid, 1,2-di(p-carboxyphenyl)ethane, 4,4'-dicarboxydiphenyl ether, and the like, as well as combinations thereof. Fused rings may also be present, for example, in 1,4- or 1,5- or 2,6-naphthalene-dicarboxylic acids. Specific examples of such aromatic polyesters may include, for example, poly(ethylene terephthalate), poly(1,4-butylene terephthalate) (PBT), poly(1,3-propylene terephthalate) (PPT), poly(1,4-butylene 2,6-naphthalate) (PBN), poly(ethylene 2,6-naphthalate) (PEN), poly(1,4-cyclohexylene dimethylene terephthalate) (PCT), as well as mixtures of the foregoing.

[0014]

[0017] Derivatives and / or copolymers of aromatic polyesters (e.g., polyethylene terephthalate) may also be used. In one embodiment, for example, modifying acids and / or modifying diols may be used to form derivatives of such polymers. As used herein, the terms "modifying acid" and "modifying diol" are intended to define compounds that can form part of the acid and diol repeat units of a polyester, respectively, and that can modify the polyester to reduce its crystallinity or make the polyester amorphous. Examples of modifying acid components include, but are not limited to, isophthalic acid, phthalic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2,6-naphthaline dicarboxylic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, suberic acid, 1,12-dodecanedioic acid, and the like. In practice, it is often preferred to use their functional acid derivatives, e.g., dimethyl, diethyl, or dipropyl esters of the dicarboxylic acids. Anhydrides or acid halides of these acids may also be used where practical. Examples of the diol component to be modified include neopentyl glycol, 1,4-cyclohexanedimethanol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, Z,8-bis(hydroxymethyltricyclo-[5.2.1.0]-decane, [wherein Z represents 3, 4 or 5]; may include, but are not limited to, 1,4-bis(2-hydroxyethoxy)benzene, 4,4'-bis(2-hydroxyethoxydiphenyl ether [bis-hydroxy-ethyl bisphenol A], 4,4'-bis(2-hydroxyethoxy)diphenyl sulfide [bis-hydroxy-ethyl bisphenol S] and diols containing one or more oxygen atoms in the chain, such as diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, and the like.Generally, these diols contain from 2 to 18 carbon atoms, and in some embodiments, from 2 to 8 carbon atoms. The alicyclic diols can be used in their cis or trans configuration, or as a mixture of both forms.

[0015]

[0018] For example, the aromatic polyesters described above typically have a DTUL value of about 40°C to about 80°C, about 45°C to about 75°C in some embodiments, and about 50°C to about 70°C in some embodiments, as determined at a load of 1.8 MPa according to ISO 75-2:2013. The aromatic polyesters also typically have a glass transition temperature of about 30°C to about 120°C, about 40°C to about 110°C in some embodiments, and about 50°C to about 100°C in some embodiments, as determined, for example, according to ISO 11357-2:2020, and a melting temperature of about 170°C to about 300°C, about 190°C to about 280°C in some embodiments, and about 210°C to about 260°C in some embodiments, as determined, for example, according to ISO 11357-2:2018. The aromatic polyester may also have an intrinsic viscosity, for example, as determined according to ISO 1628-5:1998, of from about 0.1 dl / g to about 6 dl / g, in some embodiments from about 0.2 to about 5 dl / g, and in some embodiments, from about 0.3 to about 1 dl / g.

[0016]

[0019] Polyarylene sulfide is also a suitable semi-crystalline aromatic polymer. Polyarylene sulfide may be a homopolymer or a copolymer. For example, the selective combination of dihaloaromatic compounds can result in a polyarylene sulfide copolymer containing at least two different units. For example, when p-dichlorobenzene is used in combination with m-dichlorobenzene or 4,4'-dichlorodiphenyl sulfone, a polyarylene sulfide copolymer containing a segment having the structure of the following formula can be formed:

[0017] [ka]

[0018] and a segment having the structure:

[0019] [ka]

[0020] or a segment having the structure:

[0021] [ka]

[0022]

[0020] Polyarylene sulfides may be linear, semi-linear, branched or crosslinked. Linear polyarylene sulfides usually contain 80 mol% or more of the repeating unit -(Ar-S)-. Such linear polymers may also contain small amounts of branching or crosslinking units, but the amount of branching or crosslinking units is usually less than about 1 mol% of the total monomer units of the polyarylene sulfide. Linear polyarylene sulfide polymers may be random or block copolymers containing the aforementioned repeating units. Semi-linear polyarylene sulfides may also have a crosslinked or branched structure in which a small amount of one or more monomers having three or more reactive functional groups are introduced into the polymer. As an example, the monomeric components used to form the semi-linear polyarylene sulfides may contain an amount of polyhaloaromatic compounds having two or more halogen substituents per molecule that can be utilized in preparing branched polymers. Such monomers are represented by the formula R'X nwhere each X is selected from chlorine, bromine, and iodine, n is an integer from 3 to 6, and R' is a polyvalent aromatic radical of valence n which may have up to about four methyl substituents, and the total number of carbon atoms in R' is in the range of 6 to about 16. Examples of some polyhaloaromatic compounds having more than two substituted halogens per molecule that can be used to form semi-linear polyarylene sulfides include 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, 1,3-dichloro-5-bromobenzene, 1,2,4-triiodobenzene, 1,2,3,5-tetrabromobenzene, hexachlorobenzene, 1,3,5-trichloro-2,4,6-trimethylbenzene, 2,2',4,4'-tetrachlorobiphenyl, 2,2',5,5'-tetra-iodobiphenyl, 2,2',6,6'-tetrabromo-3,3',5,5'-tetramethylbiphenyl, 1,2,3,4-tetrachloronaphthalene, 1,2,4-tribromo-6-methylnaphthalene, and the like, and mixtures thereof.

[0023]

[0021] For example, the above polyarylene sulfide usually has a DTUL value of about 70°C to about 220°C, about 90°C to about 200°C in some embodiments, and about 120°C to about 180°C in some embodiments, as determined at a load of 1.8 MPa according to ISO 75-2:2013. Similarly, the polyarylene sulfide usually has a glass transition temperature of about 50°C to about 120°C, about 60°C to about 115°C in some embodiments, and about 70°C to about 110°C in some embodiments, as determined, for example, according to ISO 11357-2:2020, and a melting temperature of about 220°C to about 340°C, about 240°C to about 320°C in some embodiments, and about 260°C to about 300°C in some embodiments, as determined, for example, according to ISO 11357-3:2018.

[0024] As noted above, amorphous polymers having substantially no distinct melting point temperature may also be used. Suitable amorphous polymers, for example, are typically of the formula -R 1It may also include aromatic polycarbonates containing carbonate units of the repeating structure -OC(O)-O-. 1 At least a portion (e.g., 60% or more) of the total number of groups contains aromatic moieties, the remainder being aliphatic, cycloaliphatic or aromatic, so that the polycarbonate is aromatic in that respect. 1 is C 6~30 It may be an aromatic group, i.e., it contains at least one aromatic moiety. Typically, R 1 is the general formula HO-R 1 -OH dihydroxyaromatic compounds, for example those having the specific formula: H.O.A. 1 -Y 1 -A 2 -OH [In the formula, A 1 and A 2 are independently a monocyclic divalent aromatic group; Y 1 is a single bond, or A 2 From A 1 is a bridging group having one or more atoms separating: In one particular embodiment, the dihydroxy aromatic compound can be derived from the following formula (I):

[0025] [ka]

[0026] [In the formula, R a and R b are each independently a halogen or C 1~12 Alkyl groups, e.g., C arranged meta to the hydroxy group of each arylene group. 1~3 an alkyl group (e.g., methyl); p and q are each independently 0 to 4 (e.g., 1); X arepresents a bridging group connecting two hydroxy-substituted aromatic groups, where the bridging group and the hydroxy substituents of each C6 arylene group are arranged ortho, meta, or para (especially para) relative to each other on the C6 arylene group.

[0027] In one embodiment, X a is the formula -C(R c )(R d )-[where R c and R d are each independently hydrogen, C 1~12 Alkyl, C 1~12 Cycloalkyl, C 7~12 Arylalkyl, C 7~12 Heteroalkyl or cyclic C 7~12 Heteroarylalkyl, or a group of the formula -C(=R e )-{where, R e is divalent C 1~12 is a hydrocarbon group.} is a group. 3~18 Cycloalkylidene, C 1~25 It may also be alkylidene. Exemplary groups of this type include methylene, cyclohexylmethylene, ethylidene, neopentylidene, and isopropylidene, as well as 2-[2.2.1]-bicycloheptylidene, cyclohexylidene, cyclopentylidene, cyclododecylidene, and adamantylidene. a A specific example where is a substituted cycloalkylidene is a cyclohexylidene bridged alkyl substituted bisphenol of formula (II):

[0028] [ka]

[0029] [In the formula, R a’ and R b’ are each independently 1~12 Alkyl (e.g., C such as methyl) 1~4 alkyl), optionally in the meta configuration relative to the cyclohexylidene bridging group; R g is C 1~12 Alkyl (e.g. C 1~4 alkyl) or halogen; r and s are each independently 1 to 4 (e.g., 1); t is 0 to 10, e.g., 0 to 5.

[0030]

[0024] The cyclohexylidene bridged bisphenol may be the reaction product of two moles of o-cresol with one mole of cyclohexanone. In another embodiment, the cyclohexylidene bridged bisphenol may be the reaction product of two moles of cresol with one mole of hydrogenated isophorone (e.g., 1,1,3-trimethyl-3-cyclohexan-5-one). Such cyclohexane-containing bisphenols, such as the reaction product of two moles of phenol with one mole of hydrogenated isophorone, are useful for producing polycarbonate polymers with high glass transition temperatures and high heat distortion temperatures.

[0031] In another embodiment, X a is C 1~18 Alkylene group, C 3~18 Cycloalkylene group, fused C 6~18 A cycloalkylene group or a group of formula -B 1 -WB 2 -[wherein, B 1 and B. 2 is independently C 1~6 An alkylene group, W is C 3~12 Cycloalkylidene group or C 6~16 It may also be a group represented by the formula:

[0032]

[0026] X a Also, the substituent C of the formula (III) 3~18 It may be a cycloalkylidene:

[0033] [ka]

[0034] [In the formula, R r , R p , R q and R t are each independently hydrogen, halogen, oxygen or C 1~12 is an organic group; I is a direct bond, carbon or divalent oxygen, sulfur or -N(Z)-, where Z is hydrogen, halogen, hydroxy, C 1~12 Alkyl, C 1~12 Alkoxy or C 1~12 acyl;}; h is 0 to 2; j is 1 or 2; i is 0 or 1; k is 0 to 3, where R r , R p , R q and R t at least two of the groups taken together are fused alicyclic, aromatic or heteroaromatic rings.

[0035] Other useful aromatic dihydroxyaromatic compounds include those having the formula (IV):

[0036] [ka]

[0037] [In the formula, R h are independently a halogen atom (e.g., bromine), C 1~10 Hydrocarbyl (e.g. C 1~10 Alkyl group), halogen-substituted C 1~10 Alkyl group, C 6~10 Aryl or halogen substituted C 6~10 is an aryl group; n is 0 to 4.

[0038] Specific examples of bisphenol compounds of formula (I) include, for example, 1,1-bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (hereinafter "bisphenol A" or "BPA"), 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 1,1-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)n-butane, 2,2-bis(4-hydroxy-1-methylphenyl)propane, 1,1-bis(4-hydroxy-t-butylphenyl)propane, 3,3-bis(4-hydroxyphenyl)phthalimidine, 2-phenyl-3,3-bis(4-hydroxyphenyl)phthalimidine (PPPBP), and 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane (DMBPC). In one particular embodiment, the polycarbonate has formula (I) represented by A 1 and A 2 each of Y is p-phenylene; 1 It may also be a linear homopolymer derived from bisphenol A, in which is isopropylidene.

[0039] Other examples of suitable aromatic dihydroxy compounds may include, but are not limited to, 4,4'-dihydroxybiphenyl, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, bis(4-hydroxyphenyl)methane, bis(4-hydroxyphenyl)diphenylmethane, bis(4-hydroxyphenyl)-1-naphthylmethane, 1,2-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2-(4-hydroxyphenyl)-2-(3-hydroxyphenyl)-1,2-diphenylethane, 1,3-bis(4-hydroxyphenyl)-2-(3-hydroxyphenyl)-1,2-diphenylethane, 1,4-bis(4-hydroxyphenyl)-2-(3-hydroxyphenyl)-1,2-diphenylethane, 1,5-bis(4-hydroxyphenyl)-2-(3-hydroxyphenyl)-1,2-diphenylethane, 1,6 ... bis(4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)phenylmethane, 2,2-bis(4-hydroxy-3-bromophenyl)propane, 1,1-bis(hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)isobutene, 1,1-bis(4-hydroxyphenyl)cyclododecane, trans-2,3-bis(4-hydroxyphenyl)-2-butene, 2,2-bis(4-hydroxyphenyl)adamantane, α,α'-bis(4-hydroxyphenyl)toluene Ene, bis(4-hydroxyphenyl)acetonitrile, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(3-ethyl-4-hydroxyphenyl)propane, 2,2-bis(3-n-propyl-4-hydroxyphenyl)propane, 2,2-bis(3-isopropyl-4-hydroxyphenyl)propane, 2,2-bis(3-sec-butyl-4-hydroxyphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane Pan, 2,2-bis(3-allyl-4-hydroxyphenyl)propane, 2,2-bis(3-methoxy-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)hexafluoropropane, 1,1-dichloro-2,2-bis(4-hydroxyphenyl)ethylene, 1,1-dibromo-2,2-bis(4-hydroxyphenyl)ethylene, 1,1-dichloro-2,2-bis(5-phenoxy-4-hydroxyphenyl)ethylene 4,4'-dihydroxybenzophenone, 3,3-bis(4-hydroxyphenyl)-2-butanone, 1,6-bis(4-hydroxyphenyl)-1,6-hexanedione, ethylene glycol bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfone, 9,9-bis(4-hydroxyphenyl)fluorine, 2,7-dihydroxypyrene, 6,6'-dihydroxy-3,3,3',3'-tetramethylspiro(bis)indane ("spirobiindane bisphenol"), 3,3-bis(4-hydroxyphenyl)phthalimide, 2,6-dihydroxydibenzo-p-dioxin, 2,6-dihydroxythianthrene, 2,7-dihydroxyphenoxathin, 2,7-dihydroxy-9,10-dimethylphenazine, 3,6-dihydroxydibenzofuran ... dibenzothiophene, and 2,7-dihydroxycarbazole; resorcinol; substituted resorcinol compounds such as 5-methylresorcinol, 5-ethylresorcinol, 5-propylresorcinol, 5-butylresorcinol, 5-t-butylresorcinol, 5-phenylresorcinol, 5-cumylresorcinol, 2,4,5,6-tetrafluororesorcinol, 2,4,5,6-tetrabromoresorcinol, and the like; catechol; hydroxyl; non; substituted hydroquinones, such as 2-methylhydroquinone, 2-ethylhydroquinone, 2-propylhydroquinone, 2-butylhydroquinone, 2-t-butylhydroquinone, 2-phenylhydroquinone, 2-cumylhydroquinone, 2,3,5,6-tetramethylhydroquinone, 2,3,5,6-tetra-t-butylhydroquinone, 2,3,5,6-tetrafluorohydroquinone, 2,3,5,6-tetrabromohydroquinone, and the like, as well as combinations thereof.

[0040] For example, the aromatic polycarbonate generally has a DTUL value of about 80° C. to about 300° C., in some embodiments, about 100° C. to about 250° C., and in some embodiments, about 140° C. to about 220° C., as determined at a load of 1.8 MPa according to ISO 75-2:2013. The glass transition temperature may also be, for example, about 50° C. to about 250° C., in some embodiments, about 90° C. to about 220° C., and in some embodiments, about 100° C. to about 200° C., as determined according to ISO 11357-2:2020. Such polycarbonates may also have an intrinsic viscosity of about 0.1 dl / g to about 6 dl / g, in some embodiments, about 0.2 to about 5 dl / g, and in some embodiments, about 0.3 to about 1 dl / g, as determined according to ISO 1628-4:1998.

[0041] In addition to the above-referenced polymers, highly crystalline aromatic polymers may also be used in the polymer composition. Particularly suitable examples of such polymers are liquid crystal polymers, which have a high degree of crystallinity that allows them to effectively fill small spaces in the mold. Liquid crystal polymers are generally classified as "thermotropic" insofar as they have a rod-like structure and can exhibit crystalline behavior in the molten state (e.g., in the thermotropic nematic state). Such polymers typically have a DTUL value of about 120°C to about 340°C, in some embodiments about 140°C to about 320°C, and in some embodiments about 150°C to about 300°C, as determined at a load of 1.8 MPa according to ISO 75-2:2013. The polymers also have a relatively high melting temperature, such as about 250°C to about 400°C, in some embodiments about 280°C to about 390°C, and in some embodiments about 300°C to about 380°C. As is known in the art, such polymers may be formed from one or more types of repeating units.

[0042]

[0032] The liquid crystal polymer may, for example, typically comprise one or more aromatic ester repeat units in an amount of from about 60 mol% to about 99.9 mol%, in some embodiments from about 70 mol% to about 99.5 mol%, and in some embodiments from about 80 mol% to about 99 mol% of the polymer. The aromatic ester repeat unit may generally be represented by the following formula (V):

[0043] [ka]

[0044] [In the formula, Ring B is a substituted or unsubstituted six-membered aryl group (e.g., 1,4-phenylene or 1,3-phenylene), a substituted or unsubstituted six-membered aryl group fused to a substituted or unsubstituted five- or six-membered aryl group (e.g., 2,6-naphthalene), or a substituted or unsubstituted six-membered aryl group linked to a substituted or unsubstituted five- or six-membered aryl group (e.g., 4,4-biphenylene); Y1 and Y2 are independently O, C(O), NH, C(O)HN or NHC(O).

[0045] Typically, at least one of Y1 and Y2 is C(O). Examples of such aromatic ester repeat units may include, for example, aromatic dicarboxylic acid repeat units (in formula V, Y1 and Y2 are C(O)), aromatic hydroxycarboxylic acid repeat units (in formula V, Y1 is O and Y2 is C(O)), and various combinations thereof.

[0046] For example, aromatic dicarboxylic acid repeat units derived from aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, diphenylether-4,4'-dicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, bis(4-carboxyphenyl)ether, bis(4-carboxyphenyl)butane, bis(4-carboxyphenyl)ethane, bis(3-carboxyphenyl)ether, bis(3-carboxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may be used. Particularly suitable aromatic dicarboxylic acids may include, for example, terephthalic acid ("TA"), isophthalic acid ("IA"), and 2,6-naphthalenedicarboxylic acid ("NDA"). When used, repeat units derived from aromatic dicarboxylic acids (e.g., IA, TA and / or NDA) typically comprise from about 5 mol % to about 60 mol %, in some embodiments from about 10 mol % to about 55 mol %, and in some embodiments, from about 15 mol % to about 50 mol % of the polymer.

[0047] Aromatic hydroxycarboxylic acid such as 4-hydroxybenzoic acid, 4-hydroxy-4'-biphenyl carboxylic acid, 2-hydroxy-6-naphthoic acid, 2-hydroxy-5-naphthoic acid, 3-hydroxy-2-naphthoic acid, 2-hydroxy-3-naphthoic acid, 4'-hydroxyphenyl-4-benzoic acid, 3'-hydroxyphenyl-4-benzoic acid, 4'-hydroxyphenyl-3-benzoic acid, and the like, and the aromatic hydroxycarboxyl repeating units derived from alkyl, alkoxy, aryl and halogen substitutions thereof, and combinations thereof may also be used.Particularly suitable aromatic hydroxycarboxylic acids are 4-hydroxybenzoic acid ("HBA") and 6-hydroxy-2-naphthoic acid ("HNA"). When used, repeat units derived from hydroxycarboxylic acids (e.g., HBA and / or HNA) typically comprise from about 10 mol % to about 85 mol %, in some embodiments from about 20 mol % to about 80 mol %, and in some embodiments, from about 25 mol % to about 75 mol % of the polymer.

[0048]

[0036] Other repeat units may also be used in the polymer. In some embodiments, repeat units derived from aromatic diols, such as hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl (or 4,4'-biphenol), 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, bis(4-hydroxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may be used. Particularly suitable aromatic diols may include, for example, hydroquinone ("HQ") and 4,4'-biphenol ("BP"). When used, repeat units derived from aromatic diols (e.g., HQ and / or BP) typically comprise from about 1 mol % to about 30 mol %, in some embodiments from about 2 mol % to about 25 mol %, and in some embodiments from about 5 mol % to about 20 mol % of the polymer. Repeat units, such as those derived from aromatic amides (e.g., acetaminophen ("APAP")) and / or aromatic amines (e.g., 4-aminophenol ("AP")), 3-aminophenol, 1,4-phenylenediamine, 1,3-phenylenediamine, and the like, may also be used. When used, repeat units derived from aromatic amides (e.g., APAP) and / or aromatic amines (e.g., AP) typically comprise from about 0.1 mol % to about 20 mol %, in some embodiments from about 0.5 mol % to about 15 mol %, and in some embodiments from about 1 mol % to about 10% of the polymer. It should also be understood that repeat units of various other monomers may be incorporated into the polymer. For example, in certain embodiments, the polymer may include one or more repeat units derived from non-aromatic monomers, such as aliphatic or alicyclic hydroxycarboxylic acids, dicarboxylic acids, diols, amides, amines, and the like. Of course, in other embodiments, the polymer may be "fully aromatic," in that there are no repeat units derived from non-aromatic (e.g., aliphatic or alicyclic) monomers.

[0049] In one particular embodiment, the liquid crystal polymer may be formed from repeat units derived from 4-hydroxybenzoic acid ("HBA") and terephthalic acid ("TA") and / or isophthalic acid ("IA"), as well as various other optional components. The repeat units derived from 4-hydroxybenzoic acid ("HBA") may comprise from about 10 mol % to about 80 mol %, in some embodiments from about 30 mol % to about 75 mol %, and in some embodiments from about 45 mol % to about 70 mol % of the polymer. The repeat units derived from terephthalic acid ("TA") and / or isophthalic acid ("IA") may similarly comprise from about 5 mol % to about 40 mol %, in some embodiments from about 10 mol % to about 35 mol %, and in some embodiments from about 15 mol % to about 35 mol % of the polymer. Repeat units derived from 4,4'-biphenol ("BP") and / or hydroquinone ("HQ") may also be used in amounts of about 1 mol % to about 30 mol %, in some embodiments about 2 mol % to about 25 mol %, and in some embodiments about 5 mol % to about 20 mol % of the polymer. Other possible repeat units may include those derived from 6-hydroxy-2-naphthoic acid ("HNA"), 2,6-naphthalenedicarboxylic acid ("NDA"), and / or acetaminophen ("APAP"). In certain embodiments, for example, repeat units derived from HNA, NDA, and / or APAP, if used, may each constitute about 1 mol % to about 35 mol %, in some embodiments about 2 mol % to about 30 mol %, and in some embodiments about 3 mol % to about 25 mol %.

[0050]

[0038] Of course, besides aromatic polymers, aliphatic polymers may also be suitable for use as high performance thermoplastic polymers in the polymer matrix. In one embodiment, for example, polyamides may be used, which generally have CO-NH linkages in the main chain and are obtained by condensation of aliphatic diamines with aliphatic dicarboxylic acids, by ring-opening polymerization of lactams, or by self-condensation of aminocarboxylic acids. For example, the polyamides may contain aliphatic repeating units derived from aliphatic diamines, usually having 4 to 14 carbon atoms. Examples of such diamines include straight chain aliphatic alkylenediamines such as 1,4-tetramethylenediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, etc.; branched aliphatic alkylenediamines such as 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 2,4-dimethyl-1,6-hexanediamine, 2-methyl-1,8-octanediamine, 5-methyl-1,9-nonanediamine, etc.; and combinations thereof. Aliphatic dicarboxylic acids may include, for example, adipic acid, sebacic acid, etc. Specific examples of such aliphatic polyamides include, for example, nylon-4 (poly-α-pyrrolidone), nylon-6 (polycaproamide), nylon-11 (polyundecaneamide), nylon-12 (polydodecanamide), nylon-46 (polytetramethylene adipamide), nylon-66 (polyhexamethylene adipamide), nylon-610, and nylon-612. Nylon-6 and nylon-66 are particularly suitable.

[0051] It should also be understood that it is possible to include aromatic monomer units in the polyamide so that it is considered aromatic (containing only aromatic monomer units, or both aliphatic and aromatic monomer units). Examples of aromatic dicarboxylic acids may include, for example, terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,4-phenylenedioxydiacetic acid, 1,3-phenylenedioxydiacetic acid, diphenic acid, 4,4'-oxydibenzoic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, 4,4'-biphenyldicarboxylic acid, and the like.Particularly suitable aromatic polyamides are poly(nonamethylene terephthalamide) (PA9T), poly(nonamethylene terephthalamide / nonamethylene decanediamide) (PA9T / 910), poly(nonamethylene terephthalamide / nonamethylene dodecanediamide) (PA9T / 912), poly(nonamethylene terephthalamide / 11-amino undecane amide) (PA9T / 11), poly(nonamethylene terephthalamide / 12-amino dodecane amide) (PA9T / 12), poly(decamethylene terephthalamide / 11-amino undecane amide) (PA10T / 11), poly(decamethylene terephthalamide / 12-amino dodecane amide) (PA10T / 12), poly(decamethylene terephthalamide / 11-amino undecane amide) (PA10T / 11), poly(decamethylene terephthalamide / 12-amino dodecane amide) (PA10T / 12), poly(decamethylene terephthalamide / 11-amino undecane amide) (PA10T / 12), poly(decamethylene terephthalamide / 12-amino do ... poly(decamethylene terephthalamide / hexamethylene hexanediamide) (PA10T / 66), poly(dodecamethylene terephthalamide / dodecamethylene dodecanediamide) (PA10T / 1010), poly(decamethylene terephthalamide / decamethylene dodecanediamide) (PA10T / 1012), poly(decamethylene terephthalamide / tetramethylene hexanediamide) (PA10T / 46), poly(decamethylene terephthalamide / caprolactam) (PA10T / 6), poly(decamethylene terephthalamide / hexamethylene hexanediamide) (PA10T / 66), poly(dodecamethylene terephthalamide / dodecamethylene dodecanediamide) (PA10T / 66) Poly(dodecamethylene terephthalamide / hexamethylene hexanediamide) (PA12T / 66), poly(dodecamethylene terephthalamide / caprolactam) (PA12T / 1212), poly(dodecamethylene terephthalamide / caprolactam) (PA12T / 6), poly(dodecamethylene terephthalamide / hexamethylene hexanediamide) (PA12T / 66), and the like.

[0052]

[0040] Polyamides suitable for the polymer matrix are typically crystalline or semi-crystalline in nature and therefore have a measurable melting temperature. The melting temperature may be relatively high so that the composition can impart a significant degree of heat resistance to the resulting part. For example, the polyamide may have a melting temperature of about 220°C or higher, in some embodiments about 240°C to about 325°C, and in some embodiments about 250°C to about 335°C. The polyamide may also have a relatively high glass transition temperature, such as about 30°C or higher, in some embodiments about 40°C or higher, and in some embodiments about 45°C to about 140°C. Glass transition and melting temperatures may be determined as is well known in the art, such as by ISO Test Nos. 11357-2:2020 (glass transition) and 11357-3:2018 (melting) using differential scanning calorimetry ("DSC").

[0053]

[0041] Propylene polymers may also be suitable aliphatic high performance polymers used in the polymer matrix. In general, any of a variety of propylene polymers or combinations of propylene polymers may be used in the polymer matrix, such as, for example, propylene homopolymers (e.g., syndiotactic, atactic, isotactic, etc.), propylene copolymers, etc. In one embodiment, a propylene polymer may be used that is, for example, an isotactic or syndiotactic homopolymer. In general, the term "syndiotactic" refers to a tacticity in which a significant portion (if not all) of the methyl groups are alternately on opposite sides along the polymer chain. On the other hand, the term "isotactic" generally refers to a tacticity in which a significant portion (if not all) of the methyl groups are on the same side along the polymer chain. In yet other embodiments, copolymers of propylene with α-olefin monomers may be used. Specific examples of suitable α-olefin monomers may include ethylene, 1-butene, 3-methyl-1-butene, 3,3-dimethyl-1-butene, 1-pentene, 1-pentene with one or more methyl, ethyl or propyl substituents, 1-hexene with one or more methyl, ethyl or propyl substituents, 1-heptene with one or more methyl, ethyl or propyl substituents, 1-octene with one or more methyl, ethyl or propyl substituents, 1-nonene with one or more methyl, ethyl or propyl substituents, ethyl, methyl or dimethyl substituted 1-decene, 1-dodecene, and styrene. The propylene content of such copolymers may be from about 60 mol% to about 99 mol%, in some embodiments from about 80 mol% to about 98.5 mol%, and in some embodiments from about 87 mol% to about 97.5 mol%. The α-olefin content may similarly range from about 1 mol % to about 40 mol %, in some embodiments from about 1.5 mol % to about 15 mol %, and in some embodiments, from about 2.5 mol % to about 13 mol %.

[0054] Suitable propylene polymers typically have a DTUL value of about 80° C. to about 250° C., in some embodiments about 100° C. to about 220° C., and in some embodiments about 110° C. to about 200° C., as determined according to ISO 75-2:2013 at a load of 1.8 MPa. The glass transition temperature of such polymers may also be, for example, about 10° C. to about 80° C., in some embodiments about 15° C. to about 70° C., and in some embodiments about 20° C. to about 60° C., as determined according to ISO 11357-2:2020. Furthermore, the melting temperature of such polymers may be, for example, about 50° C. to about 250° C., in some embodiments about 90° C. to about 220° C., and in some embodiments about 100° C. to about 200° C., as determined according to ISO 11357-3:2018.

[0055]

[0043] Oxymethylene polymers may also be suitable aliphatic high performance polymers used in the polymer matrix. The oxymethylene polymer may be either one or more homopolymers, copolymers or mixtures thereof. Homopolymers are prepared by polymerization of formaldehyde or equivalents of formaldehyde, such as cyclic oligomers of formaldehyde. Copolymers may include one or more comonomers commonly used to prepare polyoxymethylene compositions. Commonly used comonomers include alkylene oxides of 2 to 12 carbon atoms. If a copolymer is selected, the amount of comonomer is usually 20 weight percent or less, in some embodiments 15 weight percent or less, and in some embodiments, about 2 weight percent. Comonomers may include ethylene oxide and butylene oxide. Homopolymers and copolymers are preferably: 1) those in which the terminal hydroxy groups have been endcapped by chemical reaction to form ester or ether groups; or 2) those that are not fully endcapped but have some free hydroxy ends from the comonomer units. Typical end groups, in either case, are acetate and methoxy.

[0056] B. EMI filler

[0044] As shown above, the EMI filler is also distributed within the polymer matrix. The EMI filler may include a conductive material that can provide a desired degree of electromagnetic interference shielding. In some embodiments, for example, the material may include metals, such as stainless steel, aluminum, zinc, iron, copper, silver, nickel, gold, chromium, etc., as well as alloys or mixtures thereof; carbon (e.g., carbon fibers, carbon particles, such as graphite, carbon nanotubes, carbon black, etc.); and the like. The EMI filler may also have a variety of different morphologies, such as particles (e.g., iron powder), flakes (e.g., aluminum flakes, stainless steel flakes, etc.), or fibers.

[0057] In a particularly suitable embodiment, the EMI filler contains carbon fibers. Generally speaking, the carbon fibers may exhibit high specific thermal conductivity, for example, about 200 W / m·K or more, in some embodiments, about 500 W / m·K or more, in some embodiments, about 600 W / m·K to about 3,000 W / m·K, in some embodiments, about 800 W / m·K to about 1,500 W / m·K, and low specific electrical resistivity (single filament) of less than about 20 μΩ·m, in some embodiments, less than about 10 μΩ·m, in some embodiments, about 0.05 to about 5 μΩ·m, in some embodiments, about 0.1 to about 2 μΩ·m.

[0058] In addition to exhibiting high intrinsic thermal conductivity and low volume resistivity, such fibers generally have high tensile strength relative to their mass. For example, the tensile strength of the fibers is typically about 500 to about 10,000 MPa, in some embodiments about 600 MPa to about 4,000 MPa, and in some embodiments about 800 MPa to about 2,000 MPa, as determined, for example, according to ASTM D4018-17. The fibers may have an average diameter of about 1 to about 200 micrometers, in some embodiments about 1 to about 150 micrometers, in some embodiments about 3 to about 100 micrometers, and in some embodiments about 5 to about 50 micrometers. The fibers may be chopped or ground continuous filaments. In some embodiments, for example, the fibers may be chopped fibers, which may also have a volume average length of the fibers in the range of about 0.1 to about 15 millimeters, in some embodiments about 0.5 to about 12 millimeters, and in some embodiments about 1 to about 10 millimeters.

[0059]

[0047] The properties of carbon fibers, such as those derived from cellulose, lignin, polyacrylonitrile (PAN) and pitch, may vary. Pitch-based and PAN-based carbon fibers are particularly suitable for use in the polymer composition. In some embodiments, the carbon fibers are not coated with metal. Additionally, in some embodiments, the carbon fibers do not contain carbon nanotubes.

[0060]

[0048] In some embodiments, the carbon fibers include recycled carbon fibers. Recycled carbon fibers may be obtained by various methods known in the art. For example, in some embodiments, carbon fibers that have been formed into a carbon fiber fabric but have not been impregnated with a polymer may be broken down into individual carbon fibers, particularly short carbon fibers. An example of a process for recycling carbon fibers into short carbon fiber lengths is disclosed in German Patent Application No. 102009023529, which is incorporated herein by reference.

[0061]

[0049] In another embodiment, recycled carbon fibers are obtained from carbon fiber reinforced polymers (CFRP). One CFRP recycling technique involves subjecting waste CFRP to pyrolysis. This technique utilizes high temperatures to decompose the polymeric matrix while leaving the reinforcing fibers intact. Another type of CFRP recycling technique uses chemical agents that chemically react with the polymer matrix, degrading it and breaking it down (sometimes referred to as depolymerization) into decomposition products that may be separated from the carbon fibers, for example by dissolving the decomposition products in a solvent.

[0062]

[0050] A particularly suitable process comprises first treating the fiber-reinforced composite with a normally liquid solvent (e.g. methylene chloride) to prepare a first treated solid residue comprising the reinforcing fibers. The first treatment comprises contacting the fiber-reinforced composite with a solvent to dissolve most of the matrix into the solvent. After the first treatment, a second treatment of at least a portion of the first treated solid residue comprising the reinforcing fibers is carried out with a normally gaseous material (e.g. carbon dioxide) to prepare a second treated solid residue. The second treatment comprises contacting at least a portion of the first treated solid residue with the normally gaseous material under temperature and pressure conditions at which the normally gaseous material is in liquid or supercritical fluid form. The second treatment may be particularly useful for removing residual solvent from the first treated solid residue, and may also beneficially remove some additional residual matrix material.

[0063] The first treatment may be carried out at any convenient temperature (for example, the temperature of the solvent), but is usually carried out at a temperature below the normal boiling point of the solvent, conveniently at room temperature. The dissolution may be carried out under high pressure, but is often carried out at atmospheric pressure (approximately 1 bar). The solvent may comprise any one or any combination of two or more of the following, with or without other additional components: methylene chloride, methoxy-nonafluorobutane, 2-methyltetrahydrofuran, tetrahydrofuran, ethylene tetrachloride, n-propyl bromide, dimethyl sulfoxide, polyol ester oils, esters, ethers, acetates, acids, alkalis, amines, ketones, glycol ethers, glycol ether esters, ether esters, ester-alcohols, alcohols, halogenated hydrocarbons, paraffinic hydrocarbons, aliphatic hydrocarbons, aromatic hydrocarbons, and combinations thereof. Methylene chloride is preferred. The normally gaseous material may comprise any one or any combination of two or more of the following, with or without the presence of other components: carbon dioxide, 1,1,1,2-tetrafluoroethane, difluoromethane, pentafluoroethane, and combinations thereof. In preferred embodiments, the normally gaseous material is chemically non-reactive, and even more preferably chemically inert, to the reinforcing fibers. Carbon dioxide is preferred.

[0064]

[0052] The pressure during the second treatment may be in the range of 3 MPa to 69 MPa, for example, about 7 MPa to about 10 MPa. The temperature during the second treatment may be in the range of about 0°C to about 175°C, for example, about 20°C to about 40°C. A supercritical fluid refers to a fluid whose temperature and pressure exceed the critical temperature and critical pressure of the material, for example, a temperature of more than 31.1°C and a pressure of more than 72.9 atmospheres (7.39 MPa) in the case of carbon dioxide as a normally gaseous material. After the second treatment, the container can be rapidly depressurized to atmospheric pressure, which may solidify the normally gaseous material by gas expansion cooling. The solidified material can then be sublimated by rinsing with hot water.

[0065]

[0053] The above process is capable of producing recycled carbon fibers having similar mechanical properties as virgin carbon fibers. U.S. Patent Nos. 10,487,191; 10,610,911; and 10,829,611, which are incorporated herein by reference, describe processes for recycling carbon fibers that are suitable for producing recycled carbon fibers that may be used in the present compositions.

[0066] Surprisingly, it has been found that recycled carbon fibers, especially those obtained using the above method, cause an increase in electromagnetic wave absorption compared to virgin carbon fibers. Without wishing to be bound by theory, it is believed that the recycled fibers may be better dispersed throughout the matrix, resulting in improved absorption.

[0067] The EMI filler is typically present in an amount of about 1% to about 80% by weight of the composition, in some embodiments about 2% to about 75% by weight, in some embodiments about 5% to about 70% by weight, in some embodiments about 6% to about 60% by weight, in some embodiments about 10% to about 50% by weight, in some embodiments about 20% to about 47% by weight, in some embodiments about 30% to about 45% by weight, in some embodiments about 35% to about 43% by weight. The polymer matrix may likewise be present in an amount of about 20% to about 99% by weight, in some embodiments about 25% to about 98% by weight, in some embodiments about 30% to about 95% by weight, in some embodiments about 40% to about 94% by weight, in some embodiments about 50% to about 90% by weight of the composition. Of course, the exact amount of EMI filler will generally depend on the nature of the thermoplastic polymer(s), as well as the other components in the composition.

[0068] C. Other ingredients In addition to the components noted above, the polymer matrix may also contain a variety of other components. Examples of such optional components may include, for example, thermally conductive fillers, reinforcing fibers, impact modifiers, compatibilizers, particulate fillers (e.g., talc, mica, etc.), stabilizers (e.g., antioxidants, UV stabilizers, etc.), flame retardants, lubricants, dyes, flow control agents, pigments, and other materials added to enhance properties and processability.

[0069] In some embodiments, the polymeric compositions of the present invention are capable of achieving a high degree of thermal conductivity without the need for thermally conductive fillers. In this regard, the polymeric compositions generally do not require thermally conductive fillers added in addition to the EMI fillers. Nevertheless, in some cases, thermally conductive fillers may be used. When used, the thermally conductive filler(s) typically comprise about 20% or less by weight of the composition, in some embodiments about 10% or less by weight of the composition, and in some embodiments about 0.01% to about 5% by weight of the composition. Such thermally conductive fillers generally have a high intrinsic thermal conductivity, e.g., about 50 W / m·K or more, in some embodiments about 100 W / m·K or more, and in some embodiments about 150 W / m·K or more. Examples of such materials may include, for example, boron nitride (BN), aluminum nitride (AlN), magnesium silicon nitride (MgSiN2), graphite (e.g., expanded graphite), silicon carbide (SiC), carbon nanotubes, carbon black, metal oxides (e.g., zinc oxide, magnesium oxide, beryllium oxide, zirconium oxide, yttrium oxide, etc.), metal powders (e.g., aluminum, copper, bronze, brass, etc.), and the like, as well as combinations thereof. Thermally conductive fillers may be provided in a variety of forms, such as, for example, particulate materials, fibers, and the like. For example, particulate materials may be used having an average size (e.g., diameter or length) ranging from about 1 to about 100 micrometers, in some embodiments from about 2 to about 80 micrometers, and in some embodiments from about 5 to about 60 micrometers, as determined using laser diffraction techniques (e.g., using a Horiba LA-960 particle size distribution analyzer) according to ISO 13320:2009.

[0070] The polymeric compositions of the present invention are also capable of achieving a high degree of mechanical strength without the need for additional reinforcement (e.g., reinforcing fibers). In this regard, the polymeric compositions may generally not include additional reinforcing fibers. Nonetheless, in some cases, additional reinforcing fibers may still be used, although usually in relatively small amounts. For example, when used, the additional reinforcing fibers typically comprise no more than about 20% by weight of the composition, in some embodiments no more than about 10% by weight of the composition, and in some embodiments, from about 0.01% to about 5% by weight of the composition. Such reinforcing fibers may also generally be formed from materials that are inherently insulating, such as glass, ceramics (e.g., alumina or silica), aramids (e.g., Kevlar®), polyolefins, polyesters, and the like, as well as mixtures thereof. Glass fibers, such as, for example, E-glass, A-glass, C-glass, D-glass, AR-glass, R-glass, S1-glass, S2-glass, and the like, as well as mixtures thereof, are particularly suitable. The reinforcing fibers may be in the form of randomly distributed fibers, for example, when such fibers are melt blended with the high performance polymer(s) during the formation of the polymer matrix. Regardless, the volume average length of the reinforcing fibers may be from about 1 to about 400 micrometers, in some embodiments from about 50 to about 400 micrometers, in some embodiments from about 80 to about 250 micrometers, in some embodiments from about 100 to about 200 micrometers, and in some embodiments from about 110 to about 180 micrometers. The fibers may also have an average diameter of from about 10 to about 35 micrometers, and in some embodiments from about 15 to about 30 micrometers.

[0071] If desired, the EMI fillers and other optional components described below (e.g., thermally conductive fillers, flame retardants, stabilizers, reinforcing fibers, pigments, lubricants, etc.) may be melt blended together to form the polymer matrix. The raw materials may be fed simultaneously or sequentially into a melt blending device that dispersively blends the materials. Batch and / or continuous melt blending techniques may be used. For example, mixers / kneaders, Banbury mixers, Farrel continuous mixers, single screw extruders, twin screw extruders, roll mills, etc. may be utilized to blend the materials. One particularly suitable melt blending device is a co-rotating twin screw extruder (e.g., ZSK-30 twin screw extruder available from Werner & Pfleiderer Corporation of Ramsey, NJ). Such extruders include feed and discharge ports and can provide high intensity distributive and dispersive mixing. However, in certain other embodiments, the EMI fillers and other optional components may be combined with the polymer matrix using other techniques.

[0072] II. Electronic Module

[0060] As indicated above, the polymer composition may be used in an electronic module that may include a housing, at least one electronic component (e.g., an antenna element) mounted in the housing, and an electromagnetic interference (EMI) shield mounted on a first side of the antenna element. In some embodiments, the EMI shield may be formed from the polymer composition. The EMI shield may be transparent and / or may include at least one opening configured to allow the passage of radio waves between at least one antenna element. For example, when used in a radar module, the polymer composition is particularly suitable for use in EMI shielding because it can have both EMI shielding properties and electromagnetic absorption rates, allowing it to attenuate noise in radio signals reflected within the radar module. However, it should be understood that while the polymer composition is particularly suitable for forming an EMI shield, it may also be used to form other components of the radar module. For example, regardless of the particular configuration of the module, the polymer composition of the present invention may be used to form all or a portion of the housing, including the sidewall regions that form part of the housing. In particular, one benefit of the present invention is that traditional EMI metal shielding (e.g., aluminum plates) and / or heat sinks can be eliminated from the module design, thereby reducing the weight and overall cost of the module. Nevertheless, in certain other embodiments, such additional shielding and / or heat sinks may be used. For example, the module may include metal components (e.g., aluminum plates) in some cases.

[0073]

[0061] Referring to FIG. 1, an embodiment of a radar module 100 is shown that includes a housing or substrate 102 on which the components of the module 100 are mounted. The module 100 may include a printed circuit board (PCB) 104, an EMI shield 106, and a radome or cover 108 arranged in a stacked configuration and assembled together. The housing 102 may be made of plastic, optionally a polymer composition as described herein, and may be formed by injection molding. The housing 102 may be integrally formed with a shroud 116 for an electrical connector so that a shielded electrical connection may be made to the module 100. The use of a plastic material for the housing 102 may facilitate welding of the module radome or cover 108 to the housing 102 to ensure a hermetic seal. However, other methods known in the art may also be used to attach the radome to the housing. For EMI shielding purposes, the inner surface of the housing 102 may be conductive. For that purpose, the plastic material of the housing 102 may be a conductive plastic material. Alternatively, or in addition, a conductive plating or paint can be applied to the inside of the housing 102. As another alternative, a metal plate (not shown) can be secured within the inside of the housing. The housing 102 can also include integral heat stake posts 110 that are used to align the PCB 104 through the holes 122, align the EMI shield 106 through the holes 128, and hold the housing 102, PCB 104, and EMI shield 106 together. After the heat stake joint is performed with the heat stake posts 110, the bottom surface 119 of the PCB 104 is held firmly and permanently against the conductive top surface 114 of the PCB mounting shelf 112 integrally formed in the housing 102. Similarly, the EMI shield 106 is held firmly and permanently against the top surface 118 of the PCB 104. The radome 108 can be attached to the housing 102 by mating a raised boss 132 of the housing 102 with a groove in the radome 108.

[0074]

[0062] Antenna elements, such as elements 120a and 120b, may be formed on the top surface 118 of the PCB 104 and may be EMI shielded according to an example embodiment. When the EMI shield 106 is assembled over the top surface 118 of the PCB 104, the openings 124a and 124b may be positioned to surround the antenna elements 120a and 120b, thereby exposing them. Portions of the bottom surface of the EMI shield 106 located around the periphery of the openings 124a and 124b may be held tightly against the conductor lines of the PCB 104 such that the openings 124a and 124b define cavities electrically sealed to the PCB 104 above the antenna elements 120a and 120b, respectively.

[0075]

[0063] Although by no means required, the antenna elements may be configured to receive and / or transmit 5G radio frequency signals. As used herein, "5G" generally refers to high-speed data communication via radio frequency signals. 5G networks and systems are capable of communicating data at much faster rates than previous generations of data communication standards (e.g., "4G", "LTE"). For example, as used herein, "5G frequencies" can refer to frequencies that are 1.5 GHz or higher, in some embodiments, about 2.0 GHz or higher, in some embodiments, about 2.5 GHz or higher, in some embodiments, about 3.0 GHz or higher, in some embodiments, about 3 GHz to about 300 GHz or higher, in some embodiments, about 4 GHz to about 80 GHz, in some embodiments, about 5 GHz to about 80 GHz, in some embodiments, about 20 GHz to about 80 GHz, and in some embodiments, about 28 GHz to about 60 GHz. Various standards and specifications have been published that quantify the requirements for 5G communications. As an example, the International Telecommunications Union (ITU) published the International Mobile Telecommunications-2020 ("IMT-2020") standard in 2015. The IMT-2020 standard specifies various data transmission criteria for 5G (e.g., downlink and uplink data rates, latency, etc.). The IMT-2020 standard defines uplink and downlink peak data rates as the minimum data rates for uploading and downloading data that a 5G system must support. The IMT-2020 standard sets the downlink peak data rate requirement at 20 Gbit / s and the uplink peak data rate at 10 Gbit / s. As another example, the 3G-SDI standard specifies the 5G-SDI standard for 5G. rdThe Third Generation Partnership Project (3GPP) has recently announced a new standard for 5G called "5GNR". In 2018, 3GPP published "Release 15" defining "Phase 1" for the standardization of 5GNR. 3GPP defines the 5G frequency bands as "Frequency Range 1" (FR1), which generally includes frequencies below 6 GHz, and "Frequency Range 2" (FR2), as frequency bands in the range of 20-60 GHz. The antenna modules described herein may meet or qualify as "5G" under standards announced by 3GPP, such as Release 15 (2018) and / or the IMT-2020 standard.

[0076]

[0064] To achieve high-speed data communication at high frequencies, antenna elements and arrays can utilize small characteristic sizes / spacings (e.g., fine pitch technology) that can improve antenna performance. For example, the characteristic size (spacing between antenna elements, width of antenna elements), etc., generally depends on the wavelength ("λ") of the desired transmit and / or receive radio frequency propagating through the dielectric substrate on which the antenna elements are formed (e.g., nλ / 4, where n is an integer). Furthermore, beamforming and / or beamsteering may be utilized to facilitate reception and transmission across multiple frequency ranges or channels (e.g., multiple input multiple output (MIMO), massive MIMO). High-frequency 5G antenna elements can have various configurations. For example, 5G antenna elements may be or include coplanar waveguide elements, patch arrays (e.g., mesh grid patch arrays), other suitable 5G antenna configurations. Antenna elements can be configured to provide MIMO, massive MIMO capabilities, beamsteering, etc. As used herein, "massive" MIMO capabilities generally refer to providing a large number of transmit and receive channels at an antenna array, for example, 8 transmit (Tx) and 8 receive (Rx) channels (abbreviated as 8x8). Massive MIMO capabilities may also be provided at 8x8, 12x12, 16x16, 32x32, 64x64, or more.

[0077]

[0065] The antenna elements can have various configurations and arrangements and can be made using various fabrication techniques. As an example, the antenna elements and / or associated elements (e.g., ground elements, feed lines, etc.) can utilize fine pitch technology. Fine pitch technology generally refers to small or fine spacing between their components or leads. For example, the characteristic size / dimension and / or spacing between antenna elements (or between antenna elements and a ground plane) can be about 5,000 micrometers or less, in some embodiments about 3,000 micrometers or less, in some embodiments 1,500 micrometers or less, in some embodiments 750 micrometers or less (e.g., center-to-center spacing of 1.5 mm or less), 650 micrometers or less, in some embodiments 550 micrometers or less, in some embodiments 450 micrometers or less, in some embodiments 350 micrometers or less, in some embodiments 250 micrometers or less, in some embodiments 150 micrometers or less, in some embodiments 100 micrometers or less, in some embodiments 50 micrometers or less. However, it should be understood that smaller and / or larger characteristic sizes and / or spacings may also be utilized within the scope of the present disclosure. As a result of such small characteristic dimensions, the antenna module may be achieved with a large number of antenna elements in a small footprint. For example, the antenna array may have an average antenna element concentration of more than 10 antenna elements per square centimeter, in some embodiments more than 50 antenna elements per square centimeter, in some embodiments more than 200 antenna elements per square centimeter, in some embodiments more than 1,000 antenna elements per square centimeter, in some embodiments more than 3,000 antenna elements per square centimeter, and in some embodiments more than about 5,000 antenna elements per square centimeter.Such a dense arrangement of antenna elements can increase the number of channels of a MIMO function per unit area of ​​antenna area, e.g., the number of channels can correspond to (e.g., be equal to or proportional to) the number of antenna elements.

[0078]

[0066] Referring again to FIG. 1, the EMI shielding performance may be enhanced by the sidewalls 126a, 126b of the openings 124a, 124b, respectively, in the EMI shield 106. For example, the sidewalls 126a and 126b may be formed with a gentle slope with respect to the top surface of the EMI shield 106. That is, the sidewalls 126a, 126b may be formed with a certain predetermined acute angle θ with respect to the plane of the top surface of the EMI shield 106. It is noted that the reference numeral 126a is generally used to identify any of the sidewalls of the opening 124a, and the reference numeral 126b is generally used to identify any of the sidewalls of the opening 124b. Each of the sidewalls may be formed with a different angle θ, or they may be formed with the same angle θ. According to an example embodiment, the angle θ determines the shape of the shielding cavity above the antenna patch patterns 120a and 120b of the PCB 104. The angle θ is selected such that the cavity provides shielding properties in the desired application depending on the operating parameters and characteristics of the module 100. Such operating parameters and characteristics may include, for example, target radiation frequencies and / or power levels for EMI shielding. In some example embodiments, the angle θ may be selected to maximize the size of the openings 124a, 124b.

[0079] Regardless of its particular configuration, the electronic module containing the polymer composition of the present invention may be used in a wide variety of different applications. For example, the electronic module may be used in an automobile (e.g., an electric vehicle). When used in an automobile application, for example, the electronic module may be used to sense the positioning of the vehicle relative to one or more three-dimensional objects. Short-range automotive radar may be used, for example, for parking assistance, blind spot detection, and collision avoidance applications, while long-range automotive radar may be used for dynamic cruise control and cross-traffic alert applications.

[0080] The polymeric composition may also be used in other types of products. For example, in some embodiments, the polymeric composition may be provided as an integral part of an entire article or structure used in stealth applications. In other embodiments, a composite structure may have a surface "skin" incorporating the radar absorbing composition. In other embodiments, the composition material may be applied as a coating or panel to an existing surface of another composite or other article. In some embodiments, the composition may be used in a structural component of a shipping container or projectile used in stealth applications. The component may optionally be equipped with a mechanism for adjusting its angle relative to the impinging incidence angle of a radar transmitting source to maximize radar absorption. For example, the energy of the absorbed radar signal may be converted to an integrated electrical signal using a computer device to change the orientation of the component to maximize radar absorption. This may provide a means to optimize for detection from multiple radar sources from previously unknown impact directions. In some embodiments, for example, the shipping container may take the form of a ship, aircraft, or land vehicle. In other embodiments, the composition may also be used to absorb radar in detector applications where reflected radar signals require effective capture.

[0081]

[0069] The invention can be better understood with reference to the following examples. EXAMPLES

[0082] Test Method Thermal Conductivity: In-plane and out-of-plane thermal conductivity values ​​are determined in accordance with ASTM-E1461-13.

[0083] Electromagnetic interference ("EMI") shielding: EMI shielding effectiveness may be determined in a frequency range ranging from 200 MHz to 18 GHz (e.g., 5 GHz) in accordance with ASTM-D4935-18. The thickness of the part being tested may vary, for example, from 1 millimeter, 1.6 millimeters, or 3.2 millimeters. Testing may be performed using an EM-2107A test fixture for low frequencies, e.g., 30 MHz to 1.5 GHz, and an EM-2108 standard test fixture for high frequencies, e.g., 1.5 GHz to 10 GHz. These test fixtures are magnified sections of coaxial transmission lines and are available from various manufacturers, such as Electro-Metrics. EMI shielding effectiveness may also be measured in accordance with IEEE Standard 299 at frequencies from 1 GHz to 20 GHz. Measurement data relates to shielding effectiveness with plane waves (far-field EM waves), from which near-field values ​​for magnetic and electric fields may be inferred. Electromagnetic Absorption Rate: EM absorption rate may be determined according to IEEE Standard 299. The s-factor can be measured by a Vector Network Analyzer (VNA). The amount of absorption can then be calculated using the following formula: Absorbed EM=1-10 (S21 / 10) -10 (S11 / 10) where S21 and S11 are the S-factors output by a vector network analyzer.

[0084] Tensile modulus, tensile stress, and tensile elongation at break: Tensile properties may be tested according to ISO Test No. 527-1:2019 (technically equivalent to ASTM-D638-14). Modulus and strength measurements may be performed on dog-bone shaped specimen samples having a length of 170 / 190 mm, a thickness of 4 mm, and a width of 10 mm. The test temperature may be -30°C, 23°C, or 80°C, and the test speed may be 1 or 5 mm / min.

[0085] Flexural modulus, flexural elongation at break and flexural stress: Flexural properties may be tested according to ISO178:2019 (technically equivalent to ASTM-D790-17). The test may be performed with a support span of 64 mm. The test may be performed on the center section of an uncut ISO-3167 multipurpose bar. The test temperature may be -30°C, 23°C or 80°C and the test speed may be 2 mm / min.

[0086] Charpy Impact Strength: Charpy properties may be tested according to ISO179-1:2010 (technically equivalent to ASTM-D6110). The test may be performed using a Type 1 specimen size (length 80 mm, width 10 mm and thickness 4 mm). The specimen may be cut from the center section of the general purpose bar using a single tooth milling machine. The test temperature may be -30°C, 23°C or 80°C.

[0087]

[0075] Deflection Temperature Under Load (DTUL): Deflection temperature under load may be determined according to ISO 75-2:2013 (technically equivalent to ASTM-D648-07). In particular, a test specimen sample having a length of 80 mm, width of 10 mm and thickness of 4 mm may be subjected to an edgewise three-point bending test with a prescribed load (maximum outer fiber stress) of 1.8 megapascals. The test specimen may be lowered into a silicone oil bath in which the temperature is increased at 2°C / min until it is deflected 0.25 mm (0.32 mm as per ISO Test No. 75-2:2013).

[0088] Example 1 Sample 1 is a polymer composition containing 59.3% by weight nylon 66.40% by weight recycled carbon fiber, 0.4% by weight antioxidant and 0.3% by weight lubricant. The composition is formed by melt processing the ingredients in an extruder.

[0089]

[0077] Sample 1 was tested for the mechanical, thermal and electrical properties described herein, and the results are set forth in Tables 1-6 below.

[0090] [Table 1]

[0091] [Table 2]

[0092] [Table 3]

[0093] [Table 4]

[0094] [Table 5]

[0095] [Table 6]

[0096] Example 2

[0078] Sample 2 is a polymer composition containing 60% by weight polyphenylene sulfide and 40% by weight recycled carbon fiber. The composition is formed by melt processing the ingredients in an extruder.

[0097]

[0079] Sample 2 was tested for shielding effectiveness as described herein, and the results are set forth in Table 7 below.

[0098] [Table 7]

[0099]

[0080] These and other modifications and variations of the present invention can be implemented by those skilled in the art without departing from the spirit and scope of the present invention. Furthermore, it should be understood that aspects of the various embodiments can be interchanged in whole or in part. Furthermore, those skilled in the art will recognize that the above description is for illustrative purposes only and is not intended to limit the invention as further described in the appended claims.

Claims

1. 1. A polymeric composition comprising an electromagnetic interference filler distributed within a polymeric matrix comprising a thermoplastic polymer, A polymeric composition exhibiting an average absorption of greater than or equal to about 25% as determined in accordance with ASTM D4935-18 and an average electromagnetic interference shielding effectiveness of greater than or equal to about 40 decibels over the frequency range of 2 GHz to 18 GHz at a thickness of 3.2 millimeters.

2. 10. The polymer composition of claim 1, exhibiting an electromagnetic interference shielding effectiveness of about 40 decibels or greater at a frequency of 6 GHz and a thickness of 3.2 millimeters as determined according to ASTM D4935-18.

3. 10. The polymer composition of claim 1, exhibiting an average electromagnetic interference shielding effectiveness of about 50 decibels or greater at a thickness of 3.2 millimeters over the frequency range of 200 MHz to 1.5 GHz as determined according to ASTM D4935-18.

4. 10. The polymer composition of claim 1, exhibiting a thermal conductivity of greater than or equal to about 1 W / m·K, as determined according to ASTM E 1461-13.

5. Approximately 2 kJ / m2 measured at a temperature of approximately 23°C according to ISO Test No. 179-1:2010 2 The polymer composition of claim 1, exhibiting a Charpy notched impact strength of or greater.

6. 10. The polymer composition of claim 1, exhibiting a tensile strength of greater than or equal to about 100 MPa as determined according to ISO Test No. 527-1:2019 at a temperature of about 23°C.

7. 10. The polymer composition of claim 1, exhibiting a tensile modulus of about 10,000 MPa to about 40,000 MPa at a temperature of about 23° C. as determined according to ISO Test No. 527-1:2019.

8. 10. The polymer composition of claim 1, exhibiting a flexural strength of about 150 MPa to about 600 MPa at a temperature of about 23° C. as determined according to ISO Test No. 178:2019.

9. 2. The polymer composition of claim 1, wherein the thermoplastic polymer has a deflection temperature under load of about 150° C. or greater, determined according to ISO 75-2:2013 at 1.8 MPa load.

10. The polymer composition of claim 1 , wherein the thermoplastic polymer comprises an aliphatic polymer.

11. The polymer composition of claim 10 , wherein the aliphatic polymer comprises an aliphatic polyamide.

12. 10. The polymer composition of claim 1, wherein the electromagnetic interference filler comprises from about 1% to about 80% by weight of the composition and the polymer matrix comprises from about 20% to about 99% by weight of the composition.

13. The polymer composition of claim 1 , wherein the electromagnetic interference filler comprises carbon fiber.

14. 14. The polymer composition of claim 13, wherein the carbon fibers are recycled carbon fibers.

15. 15. The polymer composition of claim 14, wherein the recycled carbon fibers are produced by treating a carbon fiber reinforced polymer comprising reinforcing carbon fibers in a polymer matrix with methylene chloride to prepare a first treated solid residue comprising the reinforcing carbon fibers, and then treating the solid residue with liquid or supercritical carbon dioxide to obtain the recycled carbon fibers.

16. 14. The polymer composition of claim 13, wherein the carbon fibers have an intrinsic thermal conductivity of about 200 W / m·K or greater.

17. 14. The polymer composition of claim 13, wherein the carbon fibers have an electrical resistivity of about 20 μΩ·m or less.

18. 14. The polymer composition of claim 13, wherein the carbon fibers are derived from polyacrylonitrile.

19. 14. The polymer composition of claim 13, wherein the carbon fibers are derived from pitch.

20. 20. The polymer composition of claim 19, wherein the pitch comprises a mesophase pitch.

21. 14. The polymer composition of claim 13, wherein the carbon fibers exhibit a tensile strength of about 500 to about 10,000 MPa as determined according to ASTM D4018-17.

22. 14. The polymer composition of claim 13, wherein the carbon fibers have an average diameter of about 1 to about 200 micrometers.

23. 11. An electronic module comprising a housing, at least one electronic component mounted in the housing, and a shield mounted to a first side of the electronic component, the shield and / or the housing comprising the polymer composition of claim 1.

24. The electronic module of claim 23 , wherein the shield includes at least one opening configured to allow passage of a radio frequency signal.

25. The electronic module of claim 23 , wherein the shield comprises the polymer composition.

26. 24. The electronic module of claim 23, wherein the electronic component comprises an antenna element.

27. 24. The electronic module of claim 23, wherein the electronic module is a radar module.

28. The electronic module of claim 27 further comprising a radome mounted on the shield.

29. 1. A radar module comprising: a housing, at least one antenna element mounted in the housing, a shield mounted on a first side of the antenna element, and a radome mounted on the shield, the shield comprising a polymer composition including recycled carbon fibers distributed in a thermoplastic polymer matrix.

30. 30. The radar module of claim 29, wherein the polymer composition exhibits an average absorption of greater than or equal to about 25% and an average electromagnetic interference shielding effectiveness of greater than or equal to about 40 decibels over a frequency range of 2 GHz to 18 GHz at a thickness of 3.2 millimeters, as determined in accordance with ASTM D4935-18.

31. 30. The radar module of claim 29, wherein the polymer composition exhibits an electromagnetic interference shielding effectiveness of about 40 decibels or greater at a frequency of 6 GHz and a thickness of 3.2 millimeters as determined in accordance with ASTM D4935-18.

32. 30. The radar module of claim 29, wherein the polymer composition exhibits an average electromagnetic interference shielding effectiveness of about 50 decibels or greater at a thickness of 3.2 millimeters over the frequency range of 200 MHz to 1.5 GHz as determined according to ASTM D4935-18.

33. 30. The radar module of claim 29, wherein the polymer composition exhibits a thermal conductivity of greater than or equal to about 1 W / m·K as determined in accordance with ASTM E 1461-13.

34. 30. The radar module of claim 29, wherein the thermoplastic polymer has a deflection temperature under load of greater than or equal to about 150° C. at a load of 1.8 MPa as determined according to ISO 75-2:2013.

35. 30. The radar module of claim 29, wherein the thermoplastic polymer comprises an aliphatic polymer.

36. 36. The radar module of claim 35, wherein the aliphatic polymer comprises an aliphatic polyamide.

37. 30. The radar module of claim 29, wherein the electromagnetic interference filler comprises from about 1% to about 80% by weight of the composition and the polymer matrix comprises from about 20% to about 99% by weight of the composition.

38. 30. The radar module of claim 29, wherein the recycled carbon fiber has an intrinsic thermal conductivity of about 200 W / m·K or greater.

39. 30. The radar module of claim 29, wherein the recycled carbon fiber has an electrical resistivity of about 20 μΩ·m or less.

40. 30. The radar module of claim 29, wherein the recycled carbon fibers are derived from polyacrylonitrile.

41. 30. The radar module of claim 29, wherein the recycled carbon fibers are derived from pitch.

42. 42. The radar module of claim 41, wherein the pitch comprises mesophase pitch.

43. 30. The radar module of claim 29, wherein the recycled carbon fibers exhibit a tensile strength of about 500 to about 10,000 MPa as determined according to ASTM D4018-17.

44. 30. The radar module of claim 29, wherein the recycled carbon fibers have an average diameter of about 1 to about 200 micrometers.

45. 30. The radar module of claim 29, wherein the recycled carbon fibers are produced by treating a carbon fiber reinforced polymer comprising reinforcing carbon fibers in a polymer matrix with methylene chloride to prepare a first treated solid residue comprising the reinforcing carbon fibers, and then treating the solid residue with liquid or supercritical carbon dioxide to obtain the recycled carbon fibers.